Influence of Vacuum Condition on Generation and Transportation of a High-Intensity Pulsed Ion Beam; EAPPC with BEAMS and MEGAGAUSS, 2016 Estoril [EAPPC 2016, 6th Euro-Asian Pulsed Power Conference ; BEAMS 2016, 21st International Conference on High-Power Particle Beams ; MG-XV, 15th International Conference on Megagauss Magnetic Field Generation and Rlated Tpics] - Zhang Q.; Pushkarev A. I. Aleksandr Ivanovich; Ding L.; Zhu X. P.; Isakova Yu. I. Yulia Ivanovna; Lei M. K. (2016, 2016)
В фонде НТБ ТПУ отсутствует